Investigating Gender‐Schema Congruity Effects on Consumers' Evaluation of Anthropomorphized Products. Issue 4 (April 2014) - van den, Ellis A.; Mugge, Ruth
ABSTRACT Anthropomorphism refers to the tendency to attribute humanlike characteristics, intentions, and behavior to nonhuman artifacts. Prior research has established a product‐schema congruity effect by suggesting that successful anthropomorphism necessitates a product with schema‐congruent features next to the promotion message. This article extends this body of research for the specific case of gender anthropomorphism by proposing a gender‐schema congruity effect. Specifically, the results of two experimental studies demonstrated that when a human gender schema is primed, that is, congruent with consumers' own gender, consumers show more preferential evaluations and are more likely to perceive the product as human, even when no product‐schema congruent features are present in the product. Results indicated that perceived anthropomorphism mediates the gender‐schema congruity effect and the product‐schema congruity effect on product evaluations.